(1232) Tourism as a source of foreign exchange السياحة كمصدر للعملات الأجنبية - Gray, H. Peter (The Institute Of National Planning., 2018)
Every developing nation will be materially assisted in its development plans if it can obtain more foreign exchange at the same terms of trade or can obtain growing amounts of foreign exchange through time without (significant) deterioration of the terms of trade.